Recent Advances in Base‐Metal‐Catalyzed Carbonylation of Unactivated Alkyl Electrophiles - Li, Wei; Jiang, Donghao; Wang, Cheng; Cheng, Li‐Jie (Chinese journal of chemistry, 2023)
Transition metal‐catalyzed carbonylation reactions represent a direct and atom‐economical approach to synthesize carbonyl compounds or their derivatives by using CO as a cheap and readily available C1 feedstock. While carbonylation of C(sp 2 )‐hybridized electrophiles ( e.g ., aryl halides) is well developed, carbonylation of less reactive unactivated alkyl electrophiles remains challenging. Recently, the use of earth‐abundant base metals including Cu, Co, Mn, Fe, Ni as catalysts has enabled advances in carbonylative coupling of alkyl electrophiles for approaching diverse carbonyl compounds or their derivatives, notably, some of which are of synthetic importance but difficult to be synthesized through previous reported methods. Herein, we have summarized and discussed these recent achievements in base‐metal‐catalyzed carbonylative C—C, C—N, C—O, C—X coupling and other carbonylation reactions of unactivated alkyl electrophiles using CO as C1 source.